إجارة الوقف في ترنجانو: دراسة فقهية تحليلية - Wan Nazihah Binti Wan 'Abdul Razak (al-Jami'ah al-Islamiyah al-'Alamiyah, 2017)
This study aims to discuss the issue of leasing charitable properties (waqf) and its provisions as it is one of the important methods to invest in waqf properties. Leasing waqf is just like leasing other properties, except it has certain provisions because of the concerns to protect the properties and the public interest. This study begins by defining the meaning of waqf or charitable properties, arguments from Al-Qur'an, Al-Sunnah and Ijmā', terms and conditions, and also the types. Then, the researcher discusses the topics on leasing waqf properties according to Muslim scholars. It contains the definition of leasing and scholars' views about it particularly: who is responsible to lease waqf properties, the tenant, leasing rate, duration of leasing contract and how the contract ends. Then the study discusses the implementation of leasing waqf properties in Terengganu state which covers the analysis of practised law of waqf in this state, the organization managing waqf properties in Terengganu which is Majlis Agama Islam dan Adat Melayu Terengganu (MAIDAM), the implementation of waqf leasing, problems faced by MAIDAM in managing leasing issues and solutions proposed to address these issues. This study used the following methods: theoretical and analytical approaches, by collecting the sources related to the topic. The researcher also looks into the implementation of waqf leasing in Terengganu at MAIDAM, and then analyzes the information. The research proves that the provisions of leasing waqf properties are similar to leasing other properties except that certain provisions are needed to protect the properties of waqf. The research also reveals that there is no specific waqf law practised in the state of Terengganu except for what is stated in Sections 63-69, Administration of Islamic Religious Affairs (Terengganu) Enactment 1422H/2001M, which contains the general issues of waqf. However none of them is about the provisions of leasing waqf properties.